Foxcatcher [large type] : the true story of my brother's murder, John du Pont's madness, and the quest for Olympic gold - Schultz, Mark, 1960- (Thorndike Press, 2014)
On January 26, 1996, Olympic gold medalist Dave Schultz was shot in the back by John E. du Pont at the family's famed Foxcatcher Farm estate. Dave and his brother, Mark, were both gold medal-winning wrestlers. Du Pont was heir to a life of privilege. How did this senseless murder happen? In his fascinating, powerful memoir, Mark Schultz takes us behind the scenes at Foxcatcher Farm -- and inside the head of the wealthiest convicted murderer in history.